Digital sales channels and the relationship between product and international diversification: Evidence from going digital retail MNEs - Batsakis, Georgios; Konara, Palitha; Theoharakis, Vasilis (Wiley, 2022)
We argue that in the era of e-commerce, retail firms can simultaneously grow their product and international portfolio by adopting a multichannel strategy, that is, using digital and physical channels. Drawing on the resource bundling perspective, we argue that the previously advocated negative relationship between product and international diversification is mitigated by the retail firm's digital sales intensity. By separately examining product and international diversification across digital and physical channels, we find that while increased product diversification in physical channels relates negatively with international diversification in both physical and digital channels, increased product diversification in digital channels relates positively with international diversification in both channels. Our hypotheses are tested against a sample of 122 born physical - going digital retail MNEs over the period 2006–2016.
Keywords: digital sales; international diversification; multichannel growth strategy; product diversification; resource bundling perspective